The Second Noether Theorem on Time Scales - Agnieszka B. Malinowska; Natália Martins (Abstract and Applied Analysis)
We extend the second Noether theorem to variational problems on time scales. As corollaries we obtain the classical second Noether theorem, the second Noether theorem for the h-calculus and the second Noether theorem for the q-calculus.